Investigation into the environmental assisted crack initiation mechanism of CMSX-4 in simulated aero engine environments at 450 - 550°C. - Duarte Martinez, Fabian (Cranfield University, 2023)
The aviation industry has continued to increase the efficiency of gas turbine engines, which are now designed to operate on a wide variety of flight routes. In general, the efficiency drive has led to components spending longer times at temperatures, where accelerated corrosion can occur. This has led to a complex degradation mechanism being identified in the lower shank region under the platform of single-crystal turbine blades. This research aims to understand the mechanism of crack initiation due to the synergistic effect of stress and high temperature corrosion environments on CMSX-4 in the lower operating temperature range, 450°C - 550°C, of an aero gas turbine blade. The first part of the investigation consisted in comparing the effect of different salt deposits in a 50 ppm SO₂ - air environment at 550°C. A 50 ppm SO₂ – air concentration was considered because the air going through the lower shank is fed directly from the compressor, and not from the combustor (which is the main source of sulphur). Characterisation of the resulting scales were carried out using scanning electron microscopy, energy dispersive spectroscopy and X- ray diffraction. Results from thermodynamic modelling are also presented. The first part of the investigation showed that CMSX-4 sample under an applied stress and no applied salt did not experience accelerated corrosion attack or crack formation when exposed to 50 ppm SO₂ - air in a 400-hour period. The same observation was made for a CMSX-4 sample under an applied stress and salted with CaSO₄. Sea salt caused accelerated corrosion attack with cracks up to 1.3 mm through the substrate formed after 400 hours of exposure. Further tests using NaCl salt in 50 ppm SO₂ – air showed that cracks can initiate after just 10 minutes of exposure at 550°C. Crack growth rates are significantly reduced after two hours of exposure within a 50-hour salt cycle. Cracks with NaCl in 50 ppm SO₂ – air have also been observed at temperatures as low as 450°C. When NaCl salt was applied to CMSX-4 and exposed to air only for 50 hours, the corrosion attack was reduced considerably, and the initiation of cracks is either suppressed or significantly delayed beyond a 50-hour period. Although this PhD has only focused on a 50-hour period, longer exposure times should be carried out to determine if air exposures delay crack initiation time, or if crack initiation is completely supressed. This thesis has therefore shown that the interaction of stress, NaCl and a sulphur- containing environment are critical to cause early crack initiation in single crystal nickel-based superalloys in the temperature range 450 - 550°C. The effect of having small concentrations of moisture in the gaseous environment or as inclusions retained in the salt are still to be investigated. A working hypothesis is that that the interaction of alkali chlorides with a sulphur-containing atmosphere is the trigger to a self-sustaining cycle where metal chloride formation, vaporisation and oxidation leads to high amounts of H₂ formed at the scale/alloy interface. Potentially, the H₂ formed at the alloy/scale interface may dissociate into atomic hydrogen, and lead to hydrogen embrittlement. For further verification of this hypothesis, a set of tests have been suggested.
Keywords: Gas turbine engines; accelerated corrosion; degradation mechanism; lower shank; single-crystal turbine blades; aero gas turbine blade